Differences in the course of the judo fight in the heaviest categories between two world championships - Stankovic, N.; Bratic, M.; Nurkic, M. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
In past few years International Judo Federation introduced many changes of competition rules. They wanted to make judo more attractive for audience and to promote "positive" judo (to encourage fighters to seek ipon in every fight). Biggest change was made at the end of 2012. After the experimental period that lasted until the next World Championship in Rio de Janeiro, they confirmed the rule change and made it official for the next Olympic period. The aim of the research was to investigate the differences in the course of the fight in the heaviest categories (-100kg and +100kg) between two World Championships (Paris 2011 and Chelyabinsk 2014), held prior and after competition rules change.